2002
DOI: 10.1089/15362300260339548
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Characteristics of Cloned Calves

Abstract: To examine the possible link between endocrine status and perinatal problems related to cattle cloning, plasma concentrations of cortisol, adrenocorticotropic hormone (ACTH) and components of the insulin-like growth factor (IGF) system were compared between 13 somatic cell cloned and seven control Japanese Black calves (five produced by artificial insemination [AI] and two produced from in vitro fertilized embryos [IVP]) immediately after birth. Five cloned calves required delivery by cesarean section (C-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…All calves in this study (nuclear transfer, n ϭ 8; controls, n ϭ 9) survived delivery and the first 48-h neonatal period. Several groups have previously reported increased birth weights (Kato et al, 2000;Kubota et al, 2000;Heyman et al, 2002;Matsuzaki and Shiga, 2002) or no difference in birth weights (Wells et al, 1998(Wells et al, , 1999 in calves resulting from nuclear transfer. In the present study increased birth weights were observed in Hereford clones but not in Holstein clones, suggesting a possible donor effect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All calves in this study (nuclear transfer, n ϭ 8; controls, n ϭ 9) survived delivery and the first 48-h neonatal period. Several groups have previously reported increased birth weights (Kato et al, 2000;Kubota et al, 2000;Heyman et al, 2002;Matsuzaki and Shiga, 2002) or no difference in birth weights (Wells et al, 1998(Wells et al, , 1999 in calves resulting from nuclear transfer. In the present study increased birth weights were observed in Hereford clones but not in Holstein clones, suggesting a possible donor effect.…”
Section: Discussionmentioning
confidence: 98%
“…Fetuses derived from somatic cell nuclear-transfer that died in late gestation had anasarca and irregularities involving the heart, lungs, liver, umbilicus, and placenta (Hill et al, 1999;ChavattePalmer et al, 2002;Heyman et al, 2002). Other investigators have reported cloned calves with type I insulin-dependent diabetes , thymic hypoplasia (Renard et al, 1999), renal insufficiency (Kato et al, 2000;ChavattePalmer et al, 2002), skeletal anomalies (Kato et al, 2000), and endocrine disturbances (Matsuzaki and Shiga, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cortisol enhances estrogen synthesis in the placenta and plays a major role in the initiation of parturition (Wood 1999). Matsuzaki & Shiga (2002) reported that the plasma concentration of cortisol in neonatal clone calves was significantly lower than that in control calves, which were produced by artificial insemination and in vitro fertilization. By contrast, we found similar cortisol concentrations between vaginally delivered clone and control calves.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of parturition in pregnant cows using dexamethasone and PGF 2a has been performed in many studies on somatic clone cattle (Hill et al 1999, Matsuzaki & Shiga 2002, Pace et al 2002. This is mainly conducted to avoid dystocia due to LOS and prolonged gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation